Estudio sobre "el diálogo gráfico profesional” - Otonelo, Jorgelina Mariel (2018)
Professional ‘Dialogue’* is understood to be a continuous challenge in search of the best expression and communication to achieve comprehension of architectural language. We have implemented a way to communicate spatial ideas during the design process using the available graphic tools. An ongoing feedback between the contracting parties makes us leave the drawing’s idea as a final product aside in order to enhance the image during the process.